Design an Automatic Water Tank Filling Tool Using NodeMCU Based on the Internet of Things - Taufan Maulana Hazbi; Alfian Ma'arif (Universitas Ahmad Dahlan, 2023)
Drought is still common in Indonesia, especially in the prolonged dry season while the world's clean water reserves are only around 3%. Groundwater is a renewable natural resource, but overexploitation can cause problems such as sink holes, land subsidence, and seawater intrusion, therefore, the design of filling water tanks and automatic height meters is made as an effort to save water. these automatic water tank measurements use the Internet of Things method accessed through Blynk. An internet of things-based tool measurement system with a water level principle uses an ultrasonic HC-SR04 sensor to measure Blynk's integrated water level, using the Nodemcu ESP8266 microcontroller as the main control. The overall result of the design of the tool, the water topping up process is shown in units of percent, the ultrasonic sensor HC-SR04 displays the actual distance and water level to Blynk in cm.